FAKTOR INTERNAL DAN EKSTERNAL YANG DOMINAN MEMPENGARUHI HASIL BELAJAR MENGGAMBAR DENGAN PERANGKAT LUNAK SISWA KELAS XI TEKNIK GAMBAR BANGUNAN SMK N 1 PADANG TAHUN 2016/2017 - 2175-2182, Widia Hapnita (Universitas Negeri Padang, 2018)
Abstract—The purpose of this research is to determine the most dominant factor which influence the learning outcomes of draw learning’s result with software (Menggambar dengan Perangkat Lunak) Subject of student grade XI at Building Draw Engineering (Teknik Gambar Bangunan) SMK N 1 Padang Year 2016/2017. This research is a quantitative descriptive. The all population took account as sample (Total Sampling) which numbers are 59 student. The collected data is thorough questionnaire, it each analyzed with the likert scale which consist of 4 options, the number of questionnaires of this instrumens is 45 questions. The result of the research are: 1. Internal Factor which influence the result of draw learning is 48,87%. 2. External factor which influence the result of draw learning is 51,01%. Based on these percentage of factor, it the main factor influenced draw learning is the external factor. Keywords: Learning’s Result, Drawing, Using Software